Standardization of Specific and Non-Specific Parameters of Propolis Extract as Raw Material for Herbal Product - Yandi Syukri; Ririk Purwati; Nadia Hazami; Hady Anshory Tahmid; Annisa Fitria (EKSAKTA: Journal of Sciences and Data Analysis, 2020)
This study aims to standardize the specific and non-specific parameters of propolis extract originating from East Java, Indonesia, to fulfil the requirements as a herbal raw material. Standardization was carried out on propolis ethanol extract taken at three different harvesting times. Standardization was carried out on specific parameters including the content of dissolved compounds, chemical content of extracts and chromatogram patterns, while the non-specific parameters of the extract included water content, ash content residue, density, microbial contamination, and heavy metal contamination. Specific extract parameters showed that the water-soluble extract content was 2.1-3.5%; levels of ethanol-soluble extract 62.00-84.00%; total flavonoid levels of 0.015-0.072 mg ER / g; and total phenol content of 0.0039-0.0053 mg ER / g. Non-specific parameters indicate that the water content is 10.72-10.90%; drying losses 10.05-10.63%; total ash content of 0.08-0.65%, density of 0.88-0.89 g / mL; Pb levels from 6.55-9.01 mg / kg; Cd content of 0.50-1.22 mg / kg, Cu content of 0.82-1.13 mg / kg; the total plate number is 10 colonies / g and the yeast fungus number is 10 colonies / g. It can be concluded that propolis extract from the East Java region of Indonesia fulfills the requirements as a raw material for herbal products in Indonesia.